Проблема набуття досвіду: фізичний та символічний виміри - Городиська, Ольга Миколаївна (My University, 2022)
Вивчаючи досвід необхідно розуміти, як він відбувається, які процеси мають місце в житті людини в цей час, що людина втрачає та отримує у підсумку. Не буде перебільшенням говорити, що людина і є її досвід – вихідний, поточний та фінальний. Також необхідно підкреслити нероздільність фізичного та символічного вимірів набуття людиною досвіду, без розриву переживання з певними матеріальними носіями та часто метафоричними, сповненими образів та знаків діями суб’єкту досвіду.

When studying experience, it is necessary to understand how it happens, what processes take place in one's life at this time, what human loses and gains as a result, etc. It will not be an exaggeration to say that human is one’s experience - initial, current and final. It is also necessary to emphasize the inseparability of the physical and symbolic dimensions of the human’s experience obtaining, without breaking the experience with certain material bearers and often metaphorical, full of images and signs actions of the experience subject.
Experience obtaining problem: physical and symbolic dimensions
Keywords: людина; поріг; лімінальність; філософія; human; experience; limit; liminality